Development of a cell-based target engagement assay for pyruvate dehydrogenase kinase - Mya D. Gough; Matthew B. Robers; Cesear R. Corona; Ranjit K. Mehta; Mukesh K. Nyati; Peter L. Toogood (SLAS Discovery)
Pyruvate dehydrogenase kinases (PDHKs) are non-canonical serine/threonine kinases that regulate the pyruvate dehydrogenase complex. Given their central role in metabolism, dysregulation of PDHKs has been linked with a broad variety of pathological conditions, such as cardiovascular disease, diabetes, lactic acidosis, and cancer. While there are many small molecule PDHK inhibitors, including several that have advanced into clinical development, no PDHK inhibitor has been approved for therapeutic use for any indication. Currently the field lacks well-characterized tool compounds that can probe PDHK biology and differentiate between PDHK isoforms. Moreover, disconnects between biochemical and cell-based assays have complicated efforts to understand the biological effect of inhibiting PDHK catalytic activity. To better understand how PDHK inhibitors function in cells, we have developed a cell-based assay using NanoBRET Target Engagement technology. Here, we describe the use of NanoBRET to evaluate binding at the PDHK ATP and lipoamide sites. Using these assays, we have profiled previously described PDHK inhibitors and demonstrated the ability of NanoBRET to distinguish between PDHK inhibitors with different mechanisms of action and to elucidate isoform selectivity.